2009
DOI: 10.1074/jbc.m109.035196
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-9 Is a High Affinity IgE-binding Lectin with Anti-allergic Effect by Blocking IgE-Antigen Complex Formation

Abstract: Galectin (Gal)-9 was first described as an eosinophil chemoattractant. With the progress in research, Gal-9 has come to be known as a versatile immunomodulator that is involved in various aspects of immune regulations, and the entire picture of the function still remains elusive. To uncover as-yet unknown activity of Gal-9, we have been examining the effect of the protein in various disease animal models. Here we show that Gal-9 attenuated asthmatic reaction in guinea pigs and suppressed passivecutaneous anaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
131
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 142 publications
(142 citation statements)
references
References 40 publications
(38 reference statements)
3
131
1
1
Order By: Relevance
“…45 Galectin-9 binds to β-galactoside residues in the carbohydrate chains of IgE and can suppress allergic inflammation. 46 It exerts this activity by blocking the binding of antigens to IgE. Galectin-3 is secreted by epithelial cells and immune inflammatory cells and binds to carbohydrate chains containing β-galactoside residues.…”
Section: Galectins-3 and -9mentioning
confidence: 99%
“…45 Galectin-9 binds to β-galactoside residues in the carbohydrate chains of IgE and can suppress allergic inflammation. 46 It exerts this activity by blocking the binding of antigens to IgE. Galectin-3 is secreted by epithelial cells and immune inflammatory cells and binds to carbohydrate chains containing β-galactoside residues.…”
Section: Galectins-3 and -9mentioning
confidence: 99%
“…These two authors have the following patent related to material pertinent to this study: 'Novel modified galectin 9 proteins and use thereof' , which was applied for by GalPharma and was issued in Japan (4792390), the USA (8,268,324) …”
Section: Acknowledgementsmentioning
confidence: 99%
“…The functions of Gal-9 have been reported to include the induction of apoptosis in T-cells, particularly CD4 + Th1 and Th17 cells, and the stimulation of regulatory T-cell activity (5-7). Interestingly, Gal-9 has been tested as a potential therapeutic agent for various autoimmune diseases (7) and allergic diseases (8). Furthermore, it has been reported that Gal-9 suppresses the cell proliferation and tumor growth of various human cancer types (9,10), such as melanoma (11) and chronic myelogenous leukemia (12).…”
Section: Introductionmentioning
confidence: 99%
“…[52][53][54][55][56] Gal-9 engages with numerous cell surface receptors such as Tim-3, a variety of PDIs, and IgE. 45,57,58 The consequences of Gal-9 interactions with these diverse receptors are now being unraveled.…”
Section: Introductionmentioning
confidence: 99%